Interfacial healing behavior of CNTs/Al composites in solid-state additive forging - Zuo, Guoliang; Bai, Yu; Shi, Shuyan; Tan, Zhanqiu; Fan, Wenxue; Li, Zhiqiang; Hao, Hai (Journal of manufacturing processes, 2024)
Solid-state additive forging (SSAF) technology provides an advanced method for manufacturing large-scale, high-quality carbon nanotube reinforced aluminum (CNT/Al) composite components. This study investigates the interfacial healing behavior of ultrafine-grained 1.5 wt% CNT/Al-4Cu-1Mg joints under specific SSAF conditions, including a temperature of 485 °C, a strain of 50 %, a strain rate of 5 × 10−4 s−1, 30 min of pre-forging heat treatment, and 30 to 120 min of post-forging annealing. It examines the morphology and distribution of CNTs in the bonding joints, evaluates their effects on the microstructure and the healing of the bonding interface, and successfully develops a joint with a fully healed interface and a tensile strength of 384 MPa. The research identifies that high-temperature forging closes gaps and voids at the bonding interface and shatters the oxide layer into micro- and nano-sized fragments, enabling the direct bonding of fresh metal in localized interface areas. Then, the high density of large-angle grain boundaries and the abundance of phase boundaries in the microstructure of the joints provide shortcuts for the short-circuit diffusion of interface atoms. Additionally, the significant pinning and bridging effects of CNTs and their byproduct, Al4C3, are instrumental in reducing the softening of the joints at high temperatures. [Display omitted] •Solid-state additive forging technology achieves traceless bonding of CNT/Al composites.•Pore merging, Oxides fracturing, and Atomic short-circuit diffusion are interface healing trilogy.•CNTs and Al4C3 offer shortcuts for Atomic short-circuit diffusion and inhibit joint softening.•Dense grain and phase boundaries significantly improve the material's inherent bondability.